2016
DOI: 10.15562/bmj.v5i3.281
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Comparison of Mannitol and Hypertonic Saline for Traumatic Brain Injury (TBI) Treatment

Abstract: Traumatic Brain Injury (TBI) case is commonly found in the emergency room. TBI accompanied by increased intracranial pressure (ICP) is a neurological emergency that requires prompt and appropriate management. Hyperosmolar fluid is the main treatment in the initial management of increased ICP. Mannitol and hypertonic saline are hyperosmolar fluids which are generally used. There is no specific recommendation regarding the choice between the two fluids. From the current studies indicate that both fluids are equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[ 34 ] One of the main conservative therapies to reduce ICP for TBI patients is hyperosmolar therapy. [ 35 ] Currently, only 2 agents are used for this purpose: Mannitol and hypertonic saline (HTS). Both the fluids have no superiority among them, even though latest studies showed that HTS had more benefits than mannitol in reducing ICP.…”
Section: The Usage Of Hypertonic Sodium Lactate In Traumatic Brain Inmentioning
confidence: 99%
“…[ 34 ] One of the main conservative therapies to reduce ICP for TBI patients is hyperosmolar therapy. [ 35 ] Currently, only 2 agents are used for this purpose: Mannitol and hypertonic saline (HTS). Both the fluids have no superiority among them, even though latest studies showed that HTS had more benefits than mannitol in reducing ICP.…”
Section: The Usage Of Hypertonic Sodium Lactate In Traumatic Brain Inmentioning
confidence: 99%
“…Injured cells tend to have dysfunctional transport mechanism within plasma membrane. This leads to sodium and calcium accumulation in cytoplasm that eventually leads to cellular edema [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperosmolar fluid administration, such as mannitol or hypertonic saline, has been proven to be 955 effective in reducing ICP. While some studies favored hypertonic saline over mannitol, however it is still difficult to prove the superiority between the two fluids because of the heterogeneity of the studies; so, which is more effective remains a matter of debate [2] .…”
Section: Introductionmentioning
confidence: 99%